2017
DOI: 10.1111/pace.13170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a stepwise approach in cavotricuspid isthmus ablation for typical atrial flutter: A randomized study comparing three catheters

Abstract: With this stepwise approach, it is possible to achieve CTI block in all cases, using a single catheter without crossover, with good times of procedure and with a low complication rate. The 8-mm solid catheter is faster than the other irrigated-tip catheters. The 3.5-mm open irrigation porous-tip catheter is as effective and safe as the conventional irrigated-tip catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…For both cryoablation and RF ablation, a larger ablation tip is associated with reduced time to achieve conduction block and shorter overall procedure times. 14,20 Consequently, the small number of freezes needed to acquire conduction block further decreased the use of fluoroscopy. (1.44%) as the most frequent, followed by respiratory (0.88%), vascular (0.78%), and neurologic (0.05%) complications.…”
Section: Acute Success and Procedural Outcomesmentioning
confidence: 99%
“…For both cryoablation and RF ablation, a larger ablation tip is associated with reduced time to achieve conduction block and shorter overall procedure times. 14,20 Consequently, the small number of freezes needed to acquire conduction block further decreased the use of fluoroscopy. (1.44%) as the most frequent, followed by respiratory (0.88%), vascular (0.78%), and neurologic (0.05%) complications.…”
Section: Acute Success and Procedural Outcomesmentioning
confidence: 99%
“…The assessment of sudden death risk in patients with arrhythmogenic cardiomyopathyand of the arrhythmia burden in AF patients undergoing a rhythm-control strategy (yield of 14.6% and 16.6% in our series, respectively)is generally accepted, and we thus do not recommend revisiting such indication. Periodical 24H monitoring may indeed increase the ability of the technique to pick up AF relapses to up to 40% of cases [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the aforementioned study demonstrated no statistical difference in ablation efficacy or complications between the catheters, there was a significant difference in speed to achieve a bidirectional block between catheters . The 8‐mm ablation catheter was significantly quicker to achieve bidirectional block than both irrigated‐tip catheters after 10 minutes of radiofrequency (RF) delivery (success 68% vs 40% and 28%, P = 0.001) and 20 minutes (96% vs 70% and 70%, P = 0.002).…”
mentioning
confidence: 95%
“…A study conducted by Rubín et al., compared the outcomes of linear CTI flutter ablation between three ablation catheters: a solid large‐tip iridium‐made 8‐mm catheter, a classic 6‐hole irrigated‐tip catheter (ThermoCool®), and a new 64‐hole irrigated‐tip catheter (ThermoCool® SF). All catheters were manufactured by Biosense Webster Inc., Diamond Bar, CA, USA.…”
mentioning
confidence: 99%
See 1 more Smart Citation